DIGITAL CAMPAIGN STRATEGY OF GEMARIKAN BY INDONESIA’S MINISTRY OF MARINE AFFAIRS AND FISHERIES - Demytri Sulistyadi Wibowo; Dwi Kartikawati (PT. Jurnal Center Indonesia Publisher, 2025)
Indonesia is the world’s second-largest fish producer, yet national fish consumption remains relatively low. To address this gap, the Ministry of Marine Affairs and Fisheries launched the Gemarikan (Eat More Fish) campaign, which has recently shifted to digital platforms such as Instagram, TikTok, and YouTube to reach wider and younger audiences. This study explores the digital communication strategies used in the Gemarikan campaign, employing a constructivist paradigm and descriptive qualitative approach. Data were gathered through interviews, observation of digital channels, and document analysis at the Directorate General of Strengthening the Competitiveness of Marine and Fishery Products. Findings show that the campaign relies on persuasive, visual, collaborative, and educational messaging. While digital media enables interactive and contextual communication, effectiveness is shaped by technical and cultural factors. The study highlights the need for data-driven, adaptive digital communication strategies to promote healthy and sustainable food consumption behavior.